Diagnostic accuracy of transperineal MRI fusion biopsy in comparison to transrectal biopsy with regard to incidental histopathological findings in transurethral resection of the prostate - Dieffenbacher, Svenja; Popeneciu, Valentin; Radtke, Jan Philipp; Teber, Dogu; Hohenfellner, Markus; Hadaschik, Boris; Hatiboglu, Gencay (Urologia internationalis, 2017)
Objective: To investigate the diagnostic accuracy of transperineal MRI/transrectal ultrasound (TRUS) fusion prostate biopsy vs. transrectal prostate biopsy in transurethral resection (TUR) specimen of men undergoing TUR of the prostate (TURP) for symptomatic bladder outlet obstruction. Material and Methods: From a database of 3,509 men receiving prostate biopsy, all those undergoing TURP and negative prostate biopsy (n = 95; 45 transrectal, 50 transperineal fusion) were analysed. TURP specimens were compared with regard to incidental prostate cancer. Results: Pre- and peri-interventional parameters in transrectal vs. fusion biopsy groups for age (65.2 ± 7.8 vs. 65.5 ± 7.3 years; p = 0.84), prostate specific antigen (10.7 ± 8.5 vs. 10.9 ± 8.7 ng/mL; p = 0.93), preoperative prostate volume (72.5 ± 26.1 vs. 71.8 ± 28.1 mL; p = 0.91) and resected weight (43.7 ± 21.9 vs. 41.4 ± 20.7 g; p = 0.61) showed no significant differences. Analysing the TURP specimen, 5 incidental T1a prostate cancers were found (3 Gleason 3 + 3 = 6; 2 Gleason 3 + 4 = 7, all in the transrectal biopsy group). Although, more biopsy cores were obtained in the MRI/TRUS fusion biopsy group (26 cores [interquartile range, IQR 24-28] vs. 14 cores [IQR 12-24], p < 0.01), there was no statistical impact of the obtained number of cores (p = 0.9) on diagnostic accuracy. Statistical analyses revealed significantly better diagnostic accuracy favoring image-guided fusion biopsy (p = 0.02). Conclusions: Our findings showed that a combination of MRI-targeted and systematic transperineal prostate biopsy improves patient safety. This is associated with a combination of transperineal biopsy technique and pre-interventional MRI.